Caracterização química e física de vinhos de mesa do norte do Espírito Santo e diferente regiões do Brasil - Costa, Amanda (2016)
The Brazilian viticulture was consolidated in the mid-nineteenth century, with the introduction of american grape cultivar Isabel (Vitis labrusca) by Italian immigrants, replacing the vineyards of European grapes (Vitis vinifera). As one of the main raw materials for the preparation of table wine in Brazil, cultivating Isabel is better adapted to environmental conditions and a high production capacity and low susceptibility to major fungal diseases that attack the vine. Wines made from grapes of the species Vitis labrusca have the preference of many Brazilian consumers, so viticulture is expanding throughout the country giving the characteristics of each region for the wine made it. So the aim of this study is to characterize wines produced with Isabel grape produced in different regions. In the first experiment were evaluated wines produced in the north of the Espírito Santo state with Isabel cultivars, Bordô, and Blend (Isabel + Bordô). In the second experiment it was characterized wines produced with Isabel cultivating four states (Espírito Santo, Minas Gerais, Rio Grande do Sul, Pernambuco), and two seasons (2014 - 2015). The treatments of both experiments were composed of three replicates each, and the variables analyzed were alcohol content (°GL), total acidity and volatile (g.L-1 ), dry extract (g.L-1 ), SO2 free and total index color, tone (420nm + 520nm), polyphenols, anthocyanins (mg.L-1 ), phenolic compounds (mg.L-1 ), and organic acids. It was observed that the significant differences between the states, and in the second experiment the state of Minas Gerais stood out. In the first experiment to cultivate Bordô presented better values in relation to Isabel.